Advancements in Understanding and Mitigating Near-Earth Asteroid Threats: Technology, Classification, and Global Cooperation - Li, Jiayang (Transactions on Computer Science and Intelligent Systems Research, 2024)
The study of near-Earth asteroids (NEAs) is vital for understanding the solar system and enhancing planetary defense. By researching these asteroids, scientists gain valuable insights into planetary evolution and impact history, aiding in the prediction and prevention of potential future threats. This article introduces how advancements in technology have enabled more precise classification and analysis of NEAs, such as categorizing them into groups like Amor, Apollo, and Aten. It points out that accurate orbital analysis enhances the ability to assess collision probabilities and develop preventive measures against catastrophic impacts. Additionally, the article examines global efforts in addressing NEA threats, which involve collaboration among international organizations, government agencies, and private enterprises. Organizations like the United Nations play crucial roles in coordinating observation missions and sharing information to improve awareness and response to asteroid risks. Tools like the Torino and Palermo Scales help translate complex data into information that policymakers and the public can understand. The article also highlights those future challenges, such as the potential impact of an asteroid like Apophis, underscore the necessity for continuous observation and technological development, including methods to alter an asteroid’s path. Furthermore, the study emphasizes the importance of strengthening international cooperation through sample return missions and advanced monitoring networks to enhance global defense capabilities. In conclusion, the article underscores the critical role of global collaboration and scientific innovation in addressing NEA challenges, ensuring the long-term safety and prosperity of the planet and civilization.